Kajian Restropektif Program Pemberdayaan Ekonomi Masyarakat Pesisir - Anggraini, Oktiva (Magister Administrasi Publik (MAP) FISIPOL Universitas Gadjah Mada, 2006)
Management conservation and using of coastal resources must be achievedfor the benefit of present and future generations dependent on these resources. The paper further identifies sources of the obstacles in management coastal. Improving institutional capacity to be able of delivering good ocean policy is inevitable.The important point is that successful implementation of a national integrated coastal resources management program must involve an inter-departmental coordinating body with a dispute resolution mechanism.